Serum Neuropeptide Y Levels Are Associated with TNF-α Levels and Disease Activity in Rheumatoid Arthritis. (16th April 2020) - Ramirez-Villafaña, Melissa; Saldaña-Cruz, Ana M.; Aceves-Aceves, Javier A.; Perez-Guerrero, Edsaul E.; Fajardo-Robledo, Nicté S.; Rubio-Arellano, Edy D.; Nava-Valdivia, Cesar A.; Carrillo-Escalante, Maria O.; Totsuka-Sutto, Sylvia E.; Cardona-Müller, David; Contreras-Haro, Betsabe; Salazar-Paramo, Mario; et al.
Abstract : Background . Neuropeptide Y (NPY) is a sympathetic neurotransmitter with effects on the regulation of inflammatory cells. The role of NPY on autoimmune inflammatory diseases such as rheumatoid arthritis (RA) is not completely understood. Therefore, we evaluate if NPY levels are markers of disease activity in RA and if there is a correlation between NPY levels and tumor necrosis factor-alpha (TNF- α ), leptin, and interleukin 6 (IL-6) levels. Methods . Cross-sectional design, including 108 women with RA. We assessed disease activity by DAS28-ESR (considering active disease a score of ≥ 2.6 ). Serum NPY levels and anti-CCP2 antibody, TNF- α, IL-6, and leptin levels were quantified (ELISA). Results . Sixty-eight RA had an active disease (RA-active), and 40 were in remission (RA-remission). RA-active patients had higher NPY levels vs. RA-remission (22.8 ± 13.6 vs. 17.8 ± 10.3 ; p = 0.04 ). NPY levels correlated with increased TNF- α levels (r = 0.32, p = 0.001 ). Leptin or IL-6 did not correlate with NPY levels. In the logistic regression analysis, NPY increased the risk of disease activity (OR: 1.04, 95% CI 1.006-1.09, and p = 0.03 ). Conclusion . Higher NPY levels are an independent marker of disease activity in RA. This study encourages the quantification of NPY levels as a surrogate marker for RA-active. Future studies evaluating the role of NPY levels interacting with other proinflammatory cytokines are required.